Can a small island nation build resilience? The significance of resource‐use patterns and socio‐metabolic risks in The Bahamas. (5th January 2023) - Martin del Campo, Francisco; Singh, Simron Jit; Fishman, Tomer; Thomas, Adelle; Noll, Dominik; Drescher, Michael
Abstract: Resource‐use patterns may entail systemic risks and cascade effects, which consequently inhibit the ability to deliver socioeconomic services. Identifying resource‐use patterns exhibiting systemic risks and reshaping their combinations is a potential lever in realizing the transition to a sustainable, resilient, and resource‐secure system. Using an island context to assess the quantity and composition of resource throughput enables a more comprehensive analysis of these risks. This article presents the first mass‐balance account of socio‐metabolic flows for The Bahamas in 2018, to identify socio‐metabolic risks and cascading effects. Socio‐metabolic risks are systemic risks related to critical resource availability, material circulation integrity, and (in)equities in cost and benefit distributions. We utilize the economy‐wide material flow accounting framework to map the material flow patterns across the economy. In 2018, annual direct material input was estimated at 9.4 t/cap/yr, of which 60% were imports. High masses of waste (1.4 t/cap/yr) remained unrecovered due to the lack of recycling. Total domestic extraction (DE) were dominated by non‐metallic minerals with more than 80%, while marine biomass makes up barely 1% of total DE. Due to its linear, undiversified metabolism, and heavy imports dependency, the system is susceptible to socio‐metabolic risks and cascading effects including low levels of self‐sufficiency, high vulnerability to shocks, commodity price fluctuations, threats to sensitive ecosystems, health impacts, and economic losses, among others. A holistic resource management strategy and nature‐based solutions that consider the trade‐offs and synergies between different resource‐use patterns are critical when exploring potential plans for metabolic risk reduction.